A systematic review protocol on the use of online learning versus blended learning for teaching clinical skills to undergraduate health professional students. Issue 1 (1st January 2016) - McCutcheon, Karen; Lohan, Maria; Traynor, Marian
Abstract: Aim : This paper is a review protocol that will be used to identify, critically appraise and synthesise the best current evidence relating to the use of online learning and blended learning approaches in teaching clinical skills in undergraduate health professionals. Background : Although previous systematic reviews on online learning vs. face to face learning have been undertaken a systematic review on the impact of online learning and blended learning for teaching clinical skills has yet to be considered in undergraduate health professionals. By reviewing the students' online learning experiences, systems can potentially be designed to ensure all health professional students' are supported appropriately to meet their learning needs. Methods/design : The key objectives of the review are to evaluate how online learning teaching strategies assist students learn; to evaluate the students' satisfaction with this form of teaching; to explore the variety of online learning strategies used; to determine what online learning strategies are more effective and to determine if supplementary face to face instruction enhances learning. A search of the following databases will be made MEDLINE, CINAHL, BREI, ERIC and AUEI. This review will follow the Joanna Briggs Institute guidance for systematic reviews of quantitative and qualitative research. Conclusion : This systematic review protocol intends to support the undertaking of a systematic literature review which will report on a combination of student experience and learning outcomes therefore increasing its utility for educators and curriculum developers involved in health care education.